Spurious activation and operational integrity evaluation of redundant safety instrumented systems - Qi, Meng; Kan, Yufeng; Li, Xun; Wang, Xiaoying; Zhao, Dongfeng; Moon, Il (Reliability engineering & system safety, 2020)
•Possible scenarios leading to a spurious trip in SIS subsystems are analyzed.•A set of formulas is proposed to estimate the STR for any KooN configuration.•Investigation on the operational integrity of the SIS using numerical calculations.•Optimal KooN configurations are identified with both lower PFDavg and lower STR. Safety instrumented systems (SISs) used in various industries are designed to perform specific safety functions to prevent possible accident scenarios. However, spurious activation occurs when a SIS is activated in an untimely manner, potentially resulting in production interruption, economic loss as well as risk to present during the system restoration. Therefore, it is necessary to quantify the spurious activation rate to reduce the number of spurious activations and achieve the highest overall level of risk reduction. This study analyzes possible scenarios leading to a spurious trip in SIS subsystems and presents a further development of existing analytical formulas to calculate the spurious trip rate (STR) for any KooN configuration. The proposed formulas are compared to the existing ones to evidence the improvements and are applied in numerical calculations to investigate the operational integrity of SIS subsystems. Results indicate that common cause failure contributes to most of the STR in input elements and logic solvers, and optimal configurations with both lower PFDavg and lower STR are identified in each subsystem. The overall approach is illustrated via a simple case study and some conclusions are drawn. [Display omitted]